Aktivitas Sosial Masyarakat pada Tradisi Pertunjukan Wayang Golek: Studi Living Hadis di Kota Bogor - Rumsinah Rumsinah; Muhammad Alif (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study explores community social activities within the tradition of Wayang Golek performances as a form of living hadith in the city of Bogor. The Wayang Golek tradition reflects the practical implementation of the teachings of the Prophet Muhammad SAW in the daily lives of the Sundanese community. Using a qualitative approach, the study involved participant observation and in-depth interviews with puppeteers and audience members. The findings indicate that Wayang Golek performances function not only as cultural entertainment but also as an indirect medium for strengthening moral values, mutual cooperation, and Islamic preaching. Social activities surrounding the performances include communal interaction, preservation of local culture, and reinforcement of religious identity amid the challenges of modernization. The study further reveals that the concept of living hadith is embodied in wayang narratives that convey ethical messages aligned with the sunnah of the Prophet. These findings highlight the importance of revitalizing local cultural traditions as an effective medium for contemporary Islamic education and value transmission.